The enhanced effect of activated sludge attached to the roots of Pistia stratiotes on nutrient removal for secondary effluent - Zhou, Jian-Zhen (Water science and technology : a journal of the International Association on Water Pollution Research, 2018)
Aquatic plants are widely used for treating wastewater treatment plant secondary effluent. During this process, some residual activated sludge in the secondary effluent is intercepted and attaches to the plant roots. However, the effect of the attached activated sludge on nutrient removal in secondary effluent has up to now been unknown. Aiming at this problem, this investigation was conducted to compare the nutrient removal rates in secondary effluent by washed Pistia stratiotes (washed batch) and Pistia stratiotes with activated sludge attached to the roots (study batch). Extracellular polymeric substances (EPS) from the activated sludge attached to the roots were extracted and characterized by three-dimensional excitation emission matrix (3D-EEM) fluorescence spectroscopy. The results showed that the nutrient removal rates in the study batch were better than that in the washed batch. The 3D-EEM results showed that the protein content of EPS increased during the experiment, indicating the growth of microorganisms in the attached activated sludge. Our work demonstrated the enhanced effect of activated sludge attached to the roots of Pistia stratiotes on the removal of pollutants in secondary effluent, which is useful to guide the practical engineering of secondary effluent treatment